2006
DOI: 10.1111/j.1365-3040.2006.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Declining hydraulic efficiency as transpiring leaves desiccate: two types of response*

Abstract: The conductance of transpiring leaves to liquid water (K leaf ) was measured across a range of steady-state leaf water potentials ( Y leaf ). Manipulating the transpiration rate in excised leaves enabled us to vary Y leaf in the range -0.1 MPa to less than -1.5 MPa while using a flowmeter to monitor the transpiration stream. Employing this technique to measure how desiccation affects K leaf in 19 species, including lycophytes, ferns, gymnosperms and angiosperms, we found two characteristic responses. Three of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(153 citation statements)
references
References 47 publications
11
141
0
1
Order By: Relevance
“…2013). Yet, it is equally important to understand why coordination among these traits is often weak or absent across species, as reported here and elsewhere (angiosperms in Brodribb and Holbrook 2006; Maherali et al. 2006; angiosperms in Brodribb et al.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…2013). Yet, it is equally important to understand why coordination among these traits is often weak or absent across species, as reported here and elsewhere (angiosperms in Brodribb and Holbrook 2006; Maherali et al. 2006; angiosperms in Brodribb et al.…”
Section: Resultssupporting
confidence: 52%
“…2007; Brodribb and Jordan 2008), but also within a single species (Brodribb and Jordan 2011). In contrast, other studies have found poor coordination between these traits (angiosperms in Brodribb and Holbrook 2006; Maherali et al. 2006; angiosperms in Brodribb et al.…”
Section: Introductionmentioning
confidence: 72%
“…Moreover, this control of BS AQP activity and thereby K leaf can explain the dynamic K leaf response to changing ambient conditions, including stress, or via changes in the turgor of the BS (e.g. in response to light or temperature conditions; Brodribb and Holbrook, 2006;Sack and Holbrook, 2006;Shatil Cohen et al, 2011). The fact that BS hydraulics control the permeability of the mesophyll to water under initial stress conditions suggests the existence of a tight hydraulic connection between the BS and the mesophyll as well as feed-forward regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Xylem must, therefore, branch and taper (Coomes et al 2008) within the leaf lamina, a process that leads to the xylem itself contributing a significant resistance to the hydraulic transport pathway in the leaf. The relative contributions of xylem and mesophyll tissue to the total hydraulic resistance of the leaf can vary across species and can change with microhabitat, since light, desiccation and temperature differentially affect xylem and mesophyll tissues (Sack et al 2002;Brodribb and Holbrook 2006;Scoffoni et al 2008). A possible involvement of aquaporins in modulating the extra-xylary hydraulic resistance of leaves has also been demonstrated (Cochard et al 2007;Kaldenhoff et al 2008;Heinen et al 2009).…”
Section: The Evaporative Pathwaymentioning
confidence: 99%